What Took You so Long? An Examination of Reporting Time and Police Misconduct Complaint Dispositions. Issue 7 (3rd July 2022) - Mrozla, Thomas; Huynh, Carol; Archbold, Carol A.
ABSTRACT: This study examines if and how the promptness of reporting internal and external police misconduct influences the disposition and discipline of misconduct investigations. Data were collected from one midwestern agency. In all, 306 allegations of police misconduct spanning 12 years were collected. In addition to promptness, this study controlled for relevant police officer, complaint, and evidentiary characteristics. Although the promptness of reporting police misconduct did not influence either the disposition or discipline of the investigation, the analyses uncovered several statistically significant relationships between the independent and dependent variables. Examining the disposition, a complaint was more likely to be sustained in interactions involving one officer. In addition, internal complaints of misconduct were more likely to be sustained than complaints filed by citizens. Investigations that did not have video recordings to review were more likely to result in a sustained complaint. Regarding discipline, results showed that interactions with one officer were less likely to yield serious discipline. This is the first study to examine whether promptness in reporting police officer misconduct influences the investigation of police misconduct.